Ectopic pregnancy in simultaneous pancreas-kidney transplantation: A case report. (2016) - Yamamoto, Shinji; Nelander, Maria
Highlights: We report a case r of ectopic pregnancy after simultaneous pancreas-kidney transplantation. Ectopic pregnancy should be included in the different diagnosis in simultaneous pancreas-kidney transplantation female patients who get acute abdominal pain. Transplanted pancreas in abdomen is easily misrecognized as adipose tissue and there is high risk that the organ to get injured surgically. The operation resulted in satisfactory results without any kind of complications. Abstract: Introduction: We present a case report of ectopic pregnancy (EP) after simultaneous pancreas-kidney transplantation (SKPTx). Presentation of case: A 33-year-old female status post SKPTx suddenly got abdominal pain in the lower level. She had high human chorionic Gonadotropin test. Ultrasonography revealed that there was no fetus in the uterus but a dilated right fallopian tube, which strongly suggested ectopic pregnancy. An emergency operation was performed and a dilated right side uterine tube was found with adhesions to her transplant. Salpingectomy was performed and no visible injury to the pancreas was found by the procedure. Pathological evaluation showed ectopic pregnant fetus, and no pancreas dysfunction was observed after the operation. Discussion: This is the first case and operation report of EP after SKPTx. We should consider various causes of acute abdomen as well as several pathological condition in the transplanted pancreas such as pancreatitis, abscess, and thrombosis in vessels in the organ. Moreover, transplanted pancreas in abdomen is easily misrecognized as adipose tissue and there is high risk that the organ to get injured surgically. Conclusion: EP should be included in the different diagnosis in SKPTx female patients who get acute abdominal pain. It is highly desirable that transplant surgeon is included in the operation team for EP of these patients.